2012
DOI: 10.1002/hbm.22032
|View full text |Cite
|
Sign up to set email alerts
|

Episodic autobiographical memory in amnestic mild cognitive impairment: What are the neural correlates?

Abstract: Autobiographical memory in amnestic Mild Cognitive Impairment (aMCI) is characterized by impaired retrieval of episodic memories, but relatively preserved personal semantic knowledge.This study aimed to identify (via FDG-PET) the neural substrates of impaired episodic specificity of autobiographical memories in 35 aMCI patients compared with 24 healthy elderly controls.Significant correlations between regional cerebral activity and the proportion of episodic details in autobiographical memories from two life p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 66 publications
1
31
0
Order By: Relevance
“…However, the recent period in Eustache et al (2004) study covered the last 5 years and is therefore very different from the recent past explored here (yesterday and today), making the comparison between the two studies tricky. Another study using also the TEMPau task failed to reveal significant correlations between hippocampal metabolism and autobiographical memories experienced during the last 12 months, suggesting that the decline in autobiographical memory in early stages of AD may be due to a dysfunction of other brain regions within the autobiographical core brain network (Bastin et al, 2012), such as the posterior cingulate cortex, already associated to the decline of episodic memory performance (Chételat et al, 2003; Bastin et al, 2010), and the precuneus, involved in visual imagery (Fletcher et al, 1995). In our study, correlations were observed in some of these areas, notably the precuneus but also in the temporo-parieto-occipital junction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the recent period in Eustache et al (2004) study covered the last 5 years and is therefore very different from the recent past explored here (yesterday and today), making the comparison between the two studies tricky. Another study using also the TEMPau task failed to reveal significant correlations between hippocampal metabolism and autobiographical memories experienced during the last 12 months, suggesting that the decline in autobiographical memory in early stages of AD may be due to a dysfunction of other brain regions within the autobiographical core brain network (Bastin et al, 2012), such as the posterior cingulate cortex, already associated to the decline of episodic memory performance (Chételat et al, 2003; Bastin et al, 2010), and the precuneus, involved in visual imagery (Fletcher et al, 1995). In our study, correlations were observed in some of these areas, notably the precuneus but also in the temporo-parieto-occipital junction.…”
Section: Discussionmentioning
confidence: 99%
“…To sum up, episodic autobiographical memory is impaired in AD, even in the early stages of the disease (Murphy et al, 2008; Leyhe et al, 2009; Irish et al, 2010, 2011; Bastin et al, 2012). This deficit is mainly subserved by the dysfunction or degeneration of medial temporal areas.…”
Section: Introductionmentioning
confidence: 99%
“…Older adults remember the general gist of a memory and associated facts (i.e., recalling a schematic mental representation), but they do not construct events in specific detail (i.e., mental construction) to the same degree as younger adults, a finding replicated numerous times . A selective deficit of internal detail generation has been documented in a host of other conditions marked by MTL atrophy or excisions, including mild cognitive impairment (MCI), which specifically affects episodic memory owing to alterations of the MTL, , and temporal lobe epilepsy (TLE) involving excised or atrophied hippocampi . There is selective hippocampal involvement in constructing and integrating internal details; patients with focal hippocampal damage produce fewer internal, but not external, details when constructing events (for an exception, see Ref.…”
Section: Section One: Mental Constructionmentioning
confidence: 99%
“…We considered interindividual variability in memory ability and in executive and attention function, as these functions are the main domains of age-related cognitive changes (Craik & Salthouse, 2000;Park & Schwartz, 2000). Individual differences in memory were indexed by the participants' z-score in verbal learning performance (word-pair learning in Liège (Bastin et al, 2012), Encoding Storage Retrieval ESR test (Eustache, Desgranges, & Lalevée, 1998) …”
Section: Cognitive Testingmentioning
confidence: 99%